2021
DOI: 10.1002/cam4.4147
|View full text |Cite
|
Sign up to set email alerts
|

Worth it or not? Primary tumor resection for stage IV pancreatic cancer patients: A SEER‐based analysis of 15,836 cases

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…These ndings potentially explain the limited e cacy of PTR, chemotherapy, and radiotherapy in patients with brain metastases. Similar results will be shown, Ningzhen Fu [17] concluded that patients with brain metastases from pancreatic cancer cannot obtain survival bene ts from PTR, shuncang Zhu [21] believed that PTR could not improve the survival time of patients with lung adenocarcinoma if brain metastasis occurred. However, the use of chemotherapy has shown a certain effect in improving the survival of patients with brain metastases [22] , for example.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These ndings potentially explain the limited e cacy of PTR, chemotherapy, and radiotherapy in patients with brain metastases. Similar results will be shown, Ningzhen Fu [17] concluded that patients with brain metastases from pancreatic cancer cannot obtain survival bene ts from PTR, shuncang Zhu [21] believed that PTR could not improve the survival time of patients with lung adenocarcinoma if brain metastasis occurred. However, the use of chemotherapy has shown a certain effect in improving the survival of patients with brain metastases [22] , for example.…”
Section: Discussionsupporting
confidence: 67%
“…This underscores the consistent survival bene ts of stage IV BC patients at different time points following surgical intervention. Jianlong Jia [16] and Ningzhen Fu [17] also utilized sequential landmark analyses to account for time-related biases in their discussions of stage 4 non-small cell carcinoma and pancreatic cancer, ultimately concluding that surgery exhibited distinct advantages.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study observed that radiotherapy is no longer a risk factor for prognosis through multivariate analysis. Adjuvant chemotherapy can considerably enhance the survival of PC patients [20] . This study also proves that chemotherapy is an in uential protective factor for metastatic PC.…”
Section: Discussionmentioning
confidence: 99%
“…The largest observational evidence on this topic comes from a SEER-based analysis published in 2021 [104]. The 15,836 stage IV patients diagnosed between 1976 and 2016 were compared as follows: chemotherapy with or without primary tumor resection (9515), chemoradiation with or without primary tumor resection (699) and no treatment versus primary tumor resection only (5403).…”
Section: Overview Of Available Literature Datamentioning
confidence: 99%